2018
DOI: 10.1111/hae.13656
|View full text |Cite
|
Sign up to set email alerts
|

Accurate measurement of extended half‐life and unmodified factor VIII low levels with one‐stage FVIII assays is dependent on the matrix of calibration curves

Abstract: Introduction The monitoring of factor VIII (FVIII) replacement therapy relies on the accurate measurement of FVIII activity over a large concentration range. However, unexplained overestimation of low FVIII levels has recently been reported with extended half‐life recombinant FVIIIs. Aim The objective of this study was to confirm previous publications indicating that the reagents used to generate the calibration curves determine the accuracy of the measurement of low FVIII levels. Methods We generated FVIII ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…den Bossche et al15 demonstrated in their study that intra-assay CV ≥20% were observed in samples containing ≤30 IU/dl FVIII:C which supports our findings. This indicates it is important to have different acceptance criteria for factor levels of 10-15 IU/dl or lower as samples known to have no interfering substances have produced CV and SR outside of these acceptance criteria, although in our data cohort CV of 23.5% was calculated in FXII assay (11 IU/dl, ARP 2).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…den Bossche et al15 demonstrated in their study that intra-assay CV ≥20% were observed in samples containing ≤30 IU/dl FVIII:C which supports our findings. This indicates it is important to have different acceptance criteria for factor levels of 10-15 IU/dl or lower as samples known to have no interfering substances have produced CV and SR outside of these acceptance criteria, although in our data cohort CV of 23.5% was calculated in FXII assay (11 IU/dl, ARP 2).…”
supporting
confidence: 92%
“…14 The figure of 15% has been used as the expected reproducibility of duplicate testing observed empirically by the Center for Esoteric Testing. 14 In contrast, Van den Bossche et al 15 defined their parallelism criteria by calculating the intra-assay CV obtained with assay activity derived from different dilutions of the test sample. These authors considered; the sample and the calibration curves to be acceptably parallel over the range of the assay when the intra-assay CV was <20%.…”
Section: Discussionmentioning
confidence: 99%
“…The use of buffer as a diluent for the FIX calibrator has been known to produce discordant results at low levels 30 ; this has also been shown recently in FVIII studies. 31 Previous research has suggested that dilution of the FIX assay calibrator in buffer by the coagulation analyser could be the main reason for the progressive overestimation of lower nominal FIX levels, as this effect can be largely avoided by having the calibrator diluted in FIX-depleted plasma (Buyue and Sommer; unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…6 A recent study incorporating FVIII-deficient plasma as diluent also eliminated the overestimation seen at low levels of FVIII in samples spiked with Advate or Eloctate. 7 Higher recovery estimates of Eloctate by CSA compared to OSA at the two higher spike levels of around 20% to 30% meant several test sites were getting over-recovery relative to the acceptable limit of within 25% of target. These differences may not always be clinically significant in the context of monitoring the higher levels needed postsurgery.…”
mentioning
confidence: 98%